Blended films of carboxymethyl cellulose from papaya peel (CMCp) and corn starch - Pornchai Rachtanapun (2018)
Cellulose was extracted from papaya peels by NaOH and then modified by reacting with chloroacetic acid to obtain carboxymenthyl cellulose from the papaya peel (CMCp). Infrared (IR) spectroscopy was used to investigate changes in the functional group of the product obtained at carboxymethylation. A carbonyl peak (C=O) at 1600 cm-1, the -CH2 peak at 1420 cm-1 and the ether peak (-O-) at 1060 cm-1 on the IR spectra of CMCp increased substantially. The effect of corn starch content on the mechanical properties (tensile strength and %elongation) and water vapor permeability (WVP) of blended films of CMCp and corn starch was investigated. The addition of corn starch in the blended film resulted in an increase in tensile strength but a decrease in %elongation. The weight ratio for CMCp to corn starch of 25:75 gave the maximum tensile strength. This ratio was used to investigate the effect of plasticizer (glycerol) content on the mechanical properties and water vapor permeability (WVP). When glycerol was added to the blended films, the tensile strength decreased, but %elongation and WVP increased.